Changer les bâtiments pour changer l’enseignement. Le projet de l’université Toulouse Le Mirail dans les années 1960 - Pauline Collet (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
In the early 1960s, the architects Georges Candilis, Shadrach Woods and Alexis Josic were chosen to design the Mirail district, which was to house several tens of thousands of inhabitants in the heart of a new city that was to become the new centre of Toulouse. Universities are going through a period of crisis, with a sharp increase in the number of students and insufficient premises everywhere in France. In Toulouse, law and literature students shared the buildings in the city centre (now rue Lautmann) but the tensions linked to May 1968 and the increase in the number of students made the situation more and more complicated. The decision was taken in 1965 to move the Faculty of Arts and Humanities to the Mirail. This university project was to be built in conjunction with the neighbourhood project. The architects let their vision of the university express itself through the construction choices. It is this project that this article proposes to study.